The implementation of the PBL model to improve the eleventh-grade students' mathematics learning outcomes at SMA IT Al-Fityah Pekanbaru - Aditya Muh. Faisal; Yenita Roza; Atma Murni (State Islamic University of North Sumatra, 2024)
This research was carried out because it was triggered by the low learning outcomes of eleventh-grade students at SMA IT Al-Fityah Pekanbaru. Classroom action research using the Problem-Based Learning (PBL) model was applied to enhance mathematical learning outcomes and the learning process. The study comprised two action cycles, progressing through four stages: planning, acting, observing, and reflecting. Conducted during the odd semesters of the 2023/2024 school year, the research involved 27 students in the eleventh grade at Al-Fityah SMA IT Pekanbaru. The research instruments included learning tools (such as syllabi, lesson plans, and student worksheets) and data collection instruments in the form of teacher-student activity sheets. These were analyzed descriptively narratively, along with student mathematics learning outcome tests, which were analyzed descriptively statistically. Data analysis revealed that the learning process, when applying the Problem-Based Learning model, consistently achieved expected progress in each meeting. The results indicated an increase in the number of students reaching the minimum achievement criteria (KKM). Before implementing the action, 44.44% of students achieved minimum achievement criteria (KKM) in the knowledge aspect. This percentage rose to 55.55% in cycle I and further increased to 77.78% in cycle II. Similarly, in terms of skill competency, the percentage of students reaching KKM was 55.25% in Cycle I and increased to 74.07% in Cycle II. Overall, the application of the PBL model positively impacted the learning process for eleventh-grade students at SMA IT Al-Fityah Pekanbaru.